‘Building for the Future?’ Government and Industry Responses to the Challenges of Talent Management in China Following the GFC - Nankervis, Alan (Routledge, 2013)
China suffered minimal fallout from the global financial crisis due to its burgeoning economy and ‘socialism with Chinese characteristics’ political strategy. However, despite this, its industries face enormous human resource management (HRM) challenges associated with the country's rapid economic growth. Principal amongst these HRM challenges is the need to attract and retain crucial talent. It is likely that if Chinese industry is unsuccessful in these endeavours, the future economic growth of China may be stalled, resulting in more serious long-term outcomes. This paper explores these challenges together with some possible solutions and future research directions.